Detection and quantification of viable but non-culturable Legionella pneumophila from water samples using flow cytometry-cell sorting and quantitative PCR - Nisar, Muhammad Atif; Ross, Kirstin E.; Brown, Melissa H.; Bentham, Richard; Best, Giles; Whiley, Harriet (Frontiers in Microbiology, 2023)
Legionella pneumophila is a waterborne pathogen and, as the causative agent of Legionnaires' disease, a significant public health concern. Exposure to environmental stresses, and disinfection treatments, promotes the formation of resistant and potentially infectious viable but non-culturable (VBNC) Legionella. The management of engineered water systems to prevent Legionnaires' disease is hindered by the presence of VBNC Legionella that cannot be detected using the standard culture (ISO11731:2017-05) and quantitative polymerase reaction (ISO/TS12869:2019) methods. This study describes a novel method to quantify VBNC Legionella from environmental water samples using a “viability based flow cytometry-cell sorting and qPCR” (VFC+qPCR) assay. This protocol was then validated by quantifying the VBNC Legionella genomic load from hospital water samples. The VBNC cells were unable to be cultured on Buffered Charcoal Yeast Extract (BCYE) agar; however, their viability was confirmed through their ATP activity and ability to infect amoeba hosts. Subsequently, an assessment of the ISO11731:2017-05 pre-treatment procedure demonstrated that acid or heat treatment cause underestimation of alive Legionella population. Our results showed that these pre-treatment procedures induce culturable cells to enter a VBNC state. This may explain the observed insensitivity and lack of reproducibility often observed with the Legionella culture method. This study represents the first time that flow cytometry-cell sorting in conjunction with a qPCR assay has been used as a rapid and direct method to quantify VBNC Legionella from environmental sources. This will significantly improve future research evaluating Legionella risk management approaches for the control of Legionnaires' disease.